Meningkatkan Kesejahteraan Remaja melalui Psikoedukasi tentang Adiksi Media Sosial: Program Pengabdian Masyarakat di Sekolah Janji Baik, Tangerang Selatan: Pengabdian - Ade Ubaidah; Hifizah Nur (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The psychoeducation program aimed to develop awareness among teenagers regarding digitalization in social media use as part of a learning tool. The content explained the impact of excessive social media use on mental health, particularly among students of Janji Baik, an alternative school located in South Tangerang. The program was attended by 18 students and conducted on March 9, 2025. Result measurements indicated that 58.8% of the students were satisfied with the program in general. However, only 4 out of 18 students (22.2%) showed an increase in awareness scores regarding social media addiction behaviors based on post-test results. Although not all quantitative indicators were achieved, most participants demonstrated enhanced awareness toward healthier social media use.Future programs are expected to reach broader targets and apply more diverse methods to maximize educational impact.